Reducing delay to endovascular reperfusion after relocating a thrombolysis unit - Laugesen, Nicolaj Grønbæk; Hansen, Klaus; Højgaard, Joan; Iversen, Helle Klingenberg; Truelsen, Thomas (Frontiers in Neurology, 2022)
Background and aims Functional outcome following mechanical thrombectomy (MT) in patients with acute ischemic stroke and large vessel occlusion is time-dependent and worsens with increasing delay. Time to endovascular reperfusion is potentially modifiable with changes in organizational structure. We investigated the changes in time to reperfusion of relocating the intravenous thrombolysis (IVT) services from a non-MT center to a MT-capable center. Methods We present an observational, consecutive, retrospective, single-center cohort study of 253 stroke patients treated with MT, 2017–2019. The observation period was divided into before and after the relocation of IVT services in 2018, period 1 and period 2, respectively. The two hospitals were located 13 km apart in an urban area, and following the relocation, IVT was administered at the MT-capable center. Time metrics were registered and divided into two main intervals, namely, ambulance departure from stroke onset location to imaging (ambulance-imaging) and imaging to reperfusion (imaging-reperfusion). The interval imaging-reperfusion included inter-hospital transfer to the MT-capable center in period 1. The association of the imaging-reperfusion duration and functional outcome at 90 days was analyzed using ordinal logistic regression. Results No significant change in ambulance-imaging was observed from a median of 27 min (interquartile range [IQR] 22–37) in period 1 to 30 min (IQR 23–40) in period 2, p = 0.19, while the median time of imaging-reperfusion decreased from 173 min (IQR 137–230) to 114 min (IQR 84–152), p < 0.001. The largest absolute time reduction from imaging to reperfusion was seen from imaging to arrival at the angio suite from 89 min (IQR 76–111) to 42 min (IQR 28–63), p < 0.001, which included inter-hospital transfer in period 1. In multivariate analysis, every 10 min of increased delay from imaging to reperfusion was associated with poorer functional outcome with an adjusted odds ratio of 0.95 (95% CI: 0.95–0.98), p < 0.001. Conclusion Relocation of IVT services to an MT-capable center was the main cause of reduced time to reperfusion for patients treated with MT and was implemented without affecting prehospital transportation time. These results suggest that patient outcome can be improved by optimizing the organization of IVT and MT services in urban areas.